Regulations of Buyer's Tax Imposition before Transfer of Land Rights - Sulistyowati Sulistyowati; Devarita Devarita; Dewi Nadya Maharani (JURNAL AKTA, 2023)
Taxes have a crucial role as a source of state revenue, including in Indonesia. The principle of fairness in tax collection includes horizontal, vertical, and geographical aspects. Seller Tax and Land and Building Rights Acquisition Duty (BPHTB) are essential in transferring land rights. Final Income Tax stipulates that Seller Tax must be paid before the Deed of Sale and Purchase (AJB), while the buyer is responsible for BPHTB. The problem arises when new regulations, such as Government Regulation Number 35 of 2023 concerning General Provisions for Regional Taxes and Regional Levies, require buyers to pay taxes on the sale and purchase binding agreement (PPJB) before AJB. This goes against the principle of ownership and can present difficulties for buyers. This research uses qualitative methods with a normative approach. The results include an analysis of regulations and public opinion, focusing on the differences between PPJB and AJB and their impact on tax liabilities. Public awareness of BPHTB's tax obligations is a significant issue, with regulation changes making it challenging to understand and implement. Data is obtained through primary, secondary, and tertiary sources, including legal documents and online news.